Noninvasive Ventilation in a Pediatric Trauma Center: A Cohort Study. (February 2022) - Piastra, Marco; De Bellis, Andrea; Morena, Tony C.; De Luca, Daniele; Pezza, Lucilla; Pizza, Alessandro; Genovese, Orazio; Mancino, Aldo; Picconi, Enzo; Conti, Giorgio
Objective: To determine whether non-invasive ventilation (NIV) can avoid the need for tracheal intubation and/or reduce the duration of invasive ventilation (IMV) in previously intubated patients admitted to the pediatric intensive care unit (PICU) and developing acute hypoxemic respiratory failure (AHRF) after major traumatic injury. Study Design: A single center observational cohort study. Setting: Pediatric ICU in a University Hospital (tertiary referral Pediatric Trauma Centre) Population: During the 48-month study period, 276 patients (median age 6.4 years) with trauma were admitted to PICU; among 86 of them, who suffered from AHRF and received ventilation (IMV and/or NIV) for more than 12 hrs, 32 patients (median age 8.5 years) were treated with NIV. Inclusion/Exclusion Criteria: Inclusion criteria: at least 12 hours of NIV; exclusion criteria: patients with facial trauma or congenital malformations; patients receiving IMV <12 hours or perioperative ventilation. Measurements and Results: Among NIV patients, 27 (84, 3%) were previously on IMV, while 5 (15, 6%) could be managed exclusively with NIV. In patients with post-extubation respiratory distress, NIV was successful in 88.4% of cases. Before starting NIV, P/F ratio was 242.7 ± 71. After 8 hours of NIV treatment, a significant oxygenation improvement (PaO2/FiO2 = 354.3 ± 81; p = 0.0002) was found, with no significant changes in carbon dioxide levels. A trend toward increasing ventilation-free time has been evidenced; NIV resulted feasible and generally well tolerated. Conclusions: AHRF in trauma patients is multifactorial and may be due to many reasons, such as lung contusion, aspiration of blood or gastric contents. Systemic inflammatory response and transfusions may also contribute to hypoxia. Our pilot study strongly suggests that NIV can be applied in post-traumatic AHRF: it may successfully reduce the time of both invasive ventilation and deep sedation. Further data from controlled studies are needed to assess the advantage of NIV in pediatric trauma.